The Impact of Terrorism on Tourist Destination Choice: A Case Study of Bali and Sharm el-Sheikh - Ali, Shah (2008)
Terrorism is an enigmatic and compelling phenomenon, and its relationship with tourism is complex and multifaceted. This dissertation aimed to clarify this relationship and examined the relationship between selected factors and tourists decision-making process for destination choice. Tourists risk perception associated with terrorism served as a basis for the analysis. Tourist destinations of Bali and Sharm el-Sheikh were selected as case studies with which to examine the impact of the terrorist incidents that occurred there may have on potential tourist's decision-making process for choosing them as holiday destinations. Independent variables examined were travel experience, safety concern levels, terrorism concern levels, terrorism risk perception levels, terrorist incident awareness levels, and socio-demographic factors including age, gender, education, nationality and presence of children. Dependent variables included concern for safety in evaluating destination choice, concern for terrorism as a constraining factor when evaluating destination choice and risk perception of terrorism when evaluating either Bali or Sharm el-Sheikh as a destination choice. A paper questionnaire and an online internet questionnaire gained a sample of 204 potential tourists, with 102 respondents for Bali and 102 respondents for Sharm el-Sheikh. Data was analysed using multivariate analysis techniques. Findings showed education and travel experience to predict risk perception and terrorism concern. Gender and presence of children were predictors for safety concerns for just the Bali sample. Safety or terrorism was not a primary concern in the decision making process. Information on the terrorist incidents demonstrated some limited changes in the decision-making process. Correlations were found between risk perception levels, safety concern levels and travel experience.